2016
DOI: 10.1039/c6pp00016a
|View full text |Cite
|
Sign up to set email alerts
|

meso-Mono-[4-(1,4,7-triazacyclononanyl)]-tri(phenyl)]porphyrin and the respective zinc(ii)-complex: complete characterization and biomolecules binding abilities

Abstract: We aimed to synthesize a new series of triazacyclononanyl-porphyrins (4 and 5) with the potential ability to bind DNA. For this, the free-base porphyrin 4 and the corresponding Zn(ii)-complex 5 were synthesized by the Schiff base formation reaction. The binding ability of the porphyrin derivatives 4 and 5 with DNA from calf-thymus was studied by UV-vis and emission spectroscopy. Detailed analysis of the results suggests that the interaction of these systems most probably occurs through π-stacking and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 97 publications
2
2
0
Order By: Relevance
“…As derivatives containing peripheral complexes of Pd(II) and Pt(II) are positively charged (cationic), they have potential cationic-anionic electrostatic binding properties with DNA phosphate units, thus demonstrating a great interaction with nucleic acids, which is in Observing the absorption analyses, the successive additions of DNA to Pd(II) and Pt(II) compound solutions caused hyperchromic effects at the Soret and Q bands without a red or blue shift, indicating that the porphyrins can interact with DNA, probably via secondary interactions by external grooves around the DNA macromolecule. As derivatives containing peripheral complexes of Pd(II) and Pt(II) are positively charged (cationic), they have potential cationic-anionic electrostatic binding properties with DNA phosphate units, thus demonstrating a great interaction with nucleic acids, which is in agreement with several previous studies that reported the activity of positively charged tetrapyrrolic macrocycles [20][21][22][23].…”
Section: Binding Properties Of Dna By Uv-vis Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…As derivatives containing peripheral complexes of Pd(II) and Pt(II) are positively charged (cationic), they have potential cationic-anionic electrostatic binding properties with DNA phosphate units, thus demonstrating a great interaction with nucleic acids, which is in Observing the absorption analyses, the successive additions of DNA to Pd(II) and Pt(II) compound solutions caused hyperchromic effects at the Soret and Q bands without a red or blue shift, indicating that the porphyrins can interact with DNA, probably via secondary interactions by external grooves around the DNA macromolecule. As derivatives containing peripheral complexes of Pd(II) and Pt(II) are positively charged (cationic), they have potential cationic-anionic electrostatic binding properties with DNA phosphate units, thus demonstrating a great interaction with nucleic acids, which is in agreement with several previous studies that reported the activity of positively charged tetrapyrrolic macrocycles [20][21][22][23].…”
Section: Binding Properties Of Dna By Uv-vis Analysissupporting
confidence: 90%
“…Molecules 2023, 28, x FOR PEER REVIEW 4 of 16 agreement with several previous studies that reported the activity of positively charged tetrapyrrolic macrocycles [20][21][22][23].…”
Section: Competitive Binding Assays With Dna By Steady-state Fluoresc...supporting
confidence: 89%
“…Furthermore, the changes in intensity of the π→π* Soret transition may be due to the interaction of the aromatic structure of the tetrapyrrolic derivatives, peripheral groups, or both, which is likely because of H-bonding interactions with the DNA nucleobases. This effect is probably caused by the presence of the π-density macrocycle moiety in the structure that may interact with DNA via hydrophobic interactions, as previously reported for some cases of porphyrin derivatives, and possibly by H-bonding interactions [ 32 , 43 ].…”
Section: Resultsmentioning
confidence: 77%
“…The interaction of porphyrins with biomolecules (DNA, proteins) is the aim of a number of drug design studies . In this context, organometallic complexes are a very important class of compounds that interact with DNA .…”
Section: Introductionmentioning
confidence: 99%